Bio-evaluation of alkaloids and saponins from bitter melon: Probing more desirable compound in treating hyperglycemia and hyperlipidemia - Mahwish; Farhan Saeed; Farhana Nosheen; Qurat-ul -Ain; Bushra Niaz; Muhammad Afzaal; Kashifa Ehsan; Muzzamal Hussain; Muhammad Imran; Entessar Al Jbawi (Cogent Food & Agriculture, 2023)
AbstractBitter melon is a medicinal plant with wide-ranging health benefits. Being complex in chemical constituents, poor evidence is available to establish the exact therapeutic benefits of different phytochemicals present in bitter melon. In the present study, bitter melon fruit skin, flesh, seeds and whole fruit were assessed to estimate alkaloid and saponin contents and subsequently bio-evaluation was performed to ascertain their potential as more potent hyperglycemic and hyperlipidemic moderators for the first time. For the feeding trial, Sprague-Dawley rats were used. Bitter melon seeds have a high amount of total alkaloids, while the flesh part has maximum total saponin contents. The group of rats fed with a diet containing seeds powder showed a more prominent impact in lowering blood glucose levels and increasing serum insulin concentration in hyperglycemic and hyperlipidemic rats. The flesh part with maximum saponin contents exhibited a substantial impact in lowering cholesterol, LDL and triglycerides and increasing HDL levels. The antihyperglycemic and antihyperlipidemic activities have a direct association with the presence of these chemical constituents. Alkaloids were found to be more potent antihyperglycemic while saponins were found to be antihyperlipidemic moderators.